The relationship of host immune cells, cytokine and nitric oxide production to tumor cells in ovarian carcinoma - Murta, Beatriz Martins Tavares; Machado, Jother Soares; Zaparoli, Mateus; Lara, Vítor Carvalho; Murta, Eddie Fernando Candido (São Paulo Medical Journal, 1999)
AIMS: This brief review focuses on the current understanding of the complex relationship of tumor-associated mononuclear cells (TAMs) with neoplastic cells, summarizing their immunological efficiency, cytokine profile and production of nitric oxide (NO) in the tumor microenvironment, with current insights on how this might affect tumor growth. DATA SOURCE: Data was obtained through Medline from articles indexed during the last 10 years. The main key words used in the research were: cancer, ovarian cancer, cytokine, nitric oxide (NO), mononuclear cell, lymphocyte, macrophage. SELECTION OF STUDIES AND DATA COLLECTION: 30 studies were reviewed, which contained data regarding the production of cytokines and NO by TAMs or malignant cells, and tried to establish a correlation between these mediators and tumor growth, especially in ovarian carcinoma. DATA SUMMARY: TAMs consist mainly of macrophages and T lymphocytes which present lower proliferative indices and cytotoxicity compared to autologous blood monocytes, although they are able to release various cytokines. The profile of cytokine expression could help to explain both the immunological impairment observed in patients with advanced carcinoma diseases and the potential of TAMs to exert antitumor activity, which makes these cells an attractive target for therapeutic intervention. NO is also produced in the tumor microenvironment. Several reports in animals suggest a tumoricidal role for NO, but in human tumors its role has not been well-established and may change during tumor progression.